2015
DOI: 10.1038/cdd.2015.1
|View full text |Cite
|
Sign up to set email alerts
|

The transrepression arm of glucocorticoid receptor signaling is protective in mutant huntingtin-mediated neurodegeneration

Abstract: The unfolded protein response (UPR) occurs following the accumulation of unfolded proteins in the endoplasmic reticulum (ER) and orchestrates an intricate balance between its prosurvival and apoptotic arms to restore cellular homeostasis and integrity. However, in certain neurodegenerative diseases, the apoptotic arm of the UPR is enhanced, resulting in excessive neuronal cell death and disease progression, both of which can be overcome by modulating the UPR. Here, we describe a novel crosstalk between glucoco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 66 publications
0
15
0
Order By: Relevance
“…The STAT6 pathway is important for maintaining cellular metabolism, particularly oxidative mitochondrial metabolism. However, GDF15 increases transcriptional regulation in response to various cellular stress and metabolic changes associated with mitochondrial dysfunction (41)(42)(43)(44). Based on these findings, we speculate that metabolic changes caused by STAT6 KO are associated with increased blood levels of GDF15.…”
Section: Discussionmentioning
confidence: 71%
“…The STAT6 pathway is important for maintaining cellular metabolism, particularly oxidative mitochondrial metabolism. However, GDF15 increases transcriptional regulation in response to various cellular stress and metabolic changes associated with mitochondrial dysfunction (41)(42)(43)(44). Based on these findings, we speculate that metabolic changes caused by STAT6 KO are associated with increased blood levels of GDF15.…”
Section: Discussionmentioning
confidence: 71%
“…For example, GCs can inhibit ERS by promoting the secretion of correctly-folded proteins and degradation of misfolded proteins [ 33 ]. They also may selectively antagonize ER stress-induced apoptosis by reducing the transcription of growth differentiation factor 15 (GDF15) [ 34 ]. Furthermore, GCs can alleviate ERS response by inducing leucine zipper protein and interacting with CHOP to attenuate ERS-induced apoptotic cell death [ 11 , 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…GR can disrupt protein machinery by regulating protein chaperons particularly heat shock proteins 70 and 90 and altering protein folding [52]. Also, several studies demonstrated that GR protects cells from ER stress-induced apoptosis via ameliorating ER stress by promoting the correct folding of proteins and enhancing the removal of misfolded proteins from the ER [53,54].…”
Section: Discussionmentioning
confidence: 99%